The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1128/jvi.01551-21
|View full text |Cite
|
Sign up to set email alerts
|

Highly Neutralizing COVID-19 Convalescent Plasmas Potently Block SARS-CoV-2 Replication and Pneumonia in Syrian Hamsters

Abstract: Despite various attempts to treat SARS-CoV-2-infected patients with COVID-19-convalescent plasmas, neither appropriate approach nor clinical utility has been established. We examined the efficacy of administration of highly-neutralizing COVID-19-convalescent plasma ( hn -plasmas) and such plasma-derived IgG administration using the Syrian hamster COVID-19 model. Two hn -plasmas, which were in the best 1% of 340 neutralizing-activity-determined convalescent plasma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 61 publications
(81 reference statements)
0
23
0
Order By: Relevance
“…At a high concentration, it can completely inhibit SARS-CoV-2 infection at the single-cell level [ 18 ]. In a hamster model representing an in vivo cell infection system, the administration of convalescent plasma inhibited viral replication in the lung [ 31 ]. However, several RCTs of convalescent plasma therapy have already been conducted in countries outside Japan, but no conclusion has been reached with respect to the efficacy of convalescent plasma therapy, which is likely in part because of the heterogeneity of the types of target patients, interventions, and endpoints among trials [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…At a high concentration, it can completely inhibit SARS-CoV-2 infection at the single-cell level [ 18 ]. In a hamster model representing an in vivo cell infection system, the administration of convalescent plasma inhibited viral replication in the lung [ 31 ]. However, several RCTs of convalescent plasma therapy have already been conducted in countries outside Japan, but no conclusion has been reached with respect to the efficacy of convalescent plasma therapy, which is likely in part because of the heterogeneity of the types of target patients, interventions, and endpoints among trials [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we demonstrate that administration of a pooled human CCP with high titer of neutralizing and spike-binding antibodies, administered one day after virus inoculation, conferred therapeutic benefits to SARS-CoV-2 infected macaques in terms of moderately reduced interstitial pneumonia, despite limited effects on markers of virus replication. Therapeutic effects of CCP with high titers of neutralizing antibodies were recently also described in Syrian hamsters [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mitsuya and his group have demonstrated that, in SARS-CoV-2-infected hamster model, COVID-19-convalescent plasmas significantly reduce SARS-CoV-2 titers in the lung of Syrian hamsters and prevent pneumonia from occurring ( Fig. 3 ) [ 9 ]. Mitsuya and his group have started a randomized clinical trial to evaluate the effect of highly neutralizing COVID-19-convalescent plasma transfer to seniors and those at high risks of having severe COVID-19, which began in February 2021 in multiple medical centers in Tokyo and is ongoing.…”
Section: Battle Against the Killer Viruses: Hiv And Severe Acute Respiratory Syndrome Coronavirus 2 (Sars-cov-2)mentioning
confidence: 99%
“…While Syrian hamsters, which were SARS-CoV-2-inoculated and received control healthy plasma developed severe pneumonia by day 8 following viral inoculation (upper left), hamsters which were inoculated with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) but received COVID-19-convalescent human plasma (D43) were protected from infection by SARS-CoV-2 and developed no pneumonia (upper right). The two lower left insets show that many airway cells of the hamster had been infected with SARS-CoV-2 and stained in dark brown; however, the two lower right insets show no infection on the airway cells [ 9 ].…”
Section: Battle Against the Killer Viruses: Hiv And Severe Acute Respiratory Syndrome Coronavirus 2 (Sars-cov-2)mentioning
confidence: 99%